Calitatea vieţii la pacienţii cu afecţiuni oncologice şi patologie depresiv-anxioasǎ comorbidǎ - David, Adriana Mihaela; Năstase, Sorina (Calitatea Vieții, 2012)
This paper presents the quality of life in patients with cancer and depression-anxiety comorbidity from bio-psycho-sociospiritual point of view. The impact of the psychological component on the assessment of the quality of life is outlined, using unsystematic personal observations. The double determinism of somatic and mental pathology, with emphasis on the interference of depression and anxiety with the quality of life is reviewed and strategies about how to improve the quality of life in patients with cancer and comorbid anxiety disorders or depression are described.